Greece : Staff Report for the 2006 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2007)
This 2006 Article IV Consultation highlights that economic growth of Greece has been strong for several years, underpinned by a rapid increase in private sector credit, following the liberalization of the financial sector and the sharp drop in interest rates. In 2006, real GDP rose by an estimated 4.1 percent, driven by private domestic demand and a pickup in goods exports. The authorities have introduced a number of significant structural measures to improve product markets. These include simplified business licensing procedures for industrial firms, more flexible overtime, and liberalization of network industries.